Efektivitas Biokonversi Sampah Organik di Institut Teknologi Sumatera Menggunakan Larva Black Soldier Fly (Hermetia Illucens) - Gabriella Anggi Renca; Aulia Annas Mufti; Firdha Cahya Alam; Alfian Zurfi; Yuni Lisafitri; Irhamni (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In an effort to utilise organic waste that also has high economic value, a promising technology for processing organic waste is bioconversion using Black Soldier Fly (BSF). This research aims to determine the effect of variation in feeding rate on the nutritional content of BSF larvae, the quality of BSF larvae residue and the waste reduction index in the ITERA food waste organic waste decomposition process. The results of the research and data analysis tests show that the residue of BSF larvae does not meet the SNI 19-7030-2004 organic fertiliser quality standards in terms of phosphorus content, but the elements P, K and C/N ratio still meet the standards. Analysis of the proximate content of BSF larvae showed that the highest fat content was 0.8529 in reactor B; for the highest protein content was 12.7204 in reactor A and the highest water content was 64.1010 in reactor C. Calculation results of the waste reduction index reached the highest value of 5.94 grams per day.